HMAP Dataset 13: Galapagos Marine Reserve, Ecuador I - Castrejón, M.; Moreno, J. (Starkey, D. J.; Nicholls, J. H.)
Catch and effort statistics, sea cucumber, spiny lobster and finfish fisheries since 1961.